The P2X7 Receptor is a Master Regulator of Microparticle and Mitochondria Exchange in Mouse Microglia - Falzoni, Simonetta; Vultaggio-Poma, Valentina; Chiozzi, Paola; Tarantini, Mario; Adinolfi, Elena; Boldrini, Paola; Giuliani, Anna Lisa; Morciano, Giampaolo; Tang, Yong; Gorecki, Dariusz C; Di Virgilio, Francesco (Function (Oxford, England), 2024)
Microparticles (MPs) are secreted by all cells, where they play a key role in intercellular communication, differentiation, inflammation, and cell energy transfer. P2X7 receptor (P2X7R) activation by extracellular ATP (eATP) causes a large MP release and affects their contents in a cell-specific fashion. We investigated MP release and functional impact in microglial cells from P2X7R-WT or P2X7R-KO mice, as well as mouse microglial cell lines characterized for high (N13-P2X7RHigh) or low (N13-P2X7RLow) P2X7R expression. P2X7R stimulation promoted release of a mixed MP population enriched with naked mitochondria. Released mitochondria were taken up and incorporated into the mitochondrial network of the recipient cells in a P2X7R-dependent fashion. NLRP3 and the P2X7R itself were also delivered to the recipient cells. Microparticle transfer increased the energy level of the recipient cells and conferred a pro-inflammatory phenotype. These data show that the P2X7R is a master regulator of intercellular organelle and MP trafficking in immune cells. Graphical Abstract Graphical Abstract